Sistem Keamanan Rumah Menggunakan Sensor Passive Infrared Receiver dan SMS Gateway Berbasis Arduino - Prasetio, Yoga Randi; Satria, Budy (The Indonesian Journal of Computer Science, 2022)
Weak security systems in a house provide opportunities and opportunities for other people who are not entitled to take and steal valuables for homeowners. Based on these problems, research was carried out by making a home security system using a passive infrared receiver sensor and an Arduino-based sms gateway. The system is designed using electronic devices such as Arduino Microcontroller as data processing, PIR sensor to detect movement in the house, buzzer as an alarm and GSM 900 A module as a communication medium in the form of SMS which is connected to the homeowner's cell phone. This system works when the PIR sensor (Passive InfraRed Receiver) detects a human entering the house and then Arduino sends data in the form of an alarm from the buzzer and sends a danger sign in the form of SMS (Short Message Service). The results of the research conducted on the PIR sensor with a distance of 30-150 cm on the object movement caused an alarm to sound originating from the buzzer and SMS notifications were also successfully sent to the homeowner every time there was movement or an open door detected by the PIR sensor. This research shows that technology can be a solution to prevent crime, especially at home through a home security system using PIR sensors and SMS Gateway